2002
DOI: 10.1209/epl/i2002-00314-9
|View full text |Cite
|
Sign up to set email alerts
|

Could one find petroleum using neutrino oscillations in matter?

Abstract: PACS. 14.60.Pq -Neutrino mass and mixing (see also 12.15.Ff Quark and lepton masses and mixing). PACS. 13.15.+g -Neutrino interactions (for neutrino-lepton interactions, see 13.10). PACS. 91.35.-x -Earth's interior structure and properties.Abstract. -In neutrino physics, it is now widely believed that neutrino oscillations are influenced by the presence of matter, modifying the energy spectrum produced by a neutrino beam traversing the Earth. Here, we will discuss the reverse problem, i.e. what could be learne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Ohlsson and Winter proposed a similar study, but using matter-enhanced neutrino oscillations as a probe [41], as a means to probe search for petroleum deposits. They concluded that this was a very difficult endeavor, since this involves much lower energy neutrinos and a different means of neutrino disappearance.…”
Section: Iii1 Early Developmentsmentioning
confidence: 99%
“…Ohlsson and Winter proposed a similar study, but using matter-enhanced neutrino oscillations as a probe [41], as a means to probe search for petroleum deposits. They concluded that this was a very difficult endeavor, since this involves much lower energy neutrinos and a different means of neutrino disappearance.…”
Section: Iii1 Early Developmentsmentioning
confidence: 99%
“…Winter [1] shows that by use of a 500MeV superbeam reasonably accurate positional information can be obtained. The example of a water dense cavity is given with location sensitivity to 100 km length and size specificity of density alteration can be measured to +50 km [41]. As compared to NAT, the NOT approach differs in that it can locate the actual position of the cavity as reconstructed from a single baseline within +100 km.…”
Section: Gemini-geological Exploration With Muons Induced By Neutrinomentioning
confidence: 99%
“…Possible applications of neutrino tomography would be to complement geophysical measurements of the profile of the Earth's interior or to find large deposits of oil. 33 A realistic study of tomography indicates that a precise determination of such profiles will be challenging, with statistics being a limitation even when the neutrino oscillation parameters become precisely known. 19 To demonstrate the essential physics of tomography, we will consider an idealized example in which the neutrino oscillation parameters are known to high precision.…”
Section: The Inversion Problem: Low Density Limitmentioning
confidence: 99%